Gulo Puan Visual Brand: Medium Promotion of Gastronomic Tourism Destinations, Pampangan District, South Sumatra - Sumbo Tinarbuko; Risvi Pangestu; I Wayan Nuriarta (Mudra Jurnal Seni Budaya, 2023)
Gulo Puan is a traditional food from the Pampangan sub-district, South Sumatra Province. Its existence has sunk into the ages. Gulo Puan does not yet have a visual brand that can represent her existence. The absence of a visual brand makes people less aware of the existence of this gastronomy. The purpose of this study is to present the Gulo Puan visual brand as a promotional medium for the gastronomic tourism destination "Guwan" Gulo Puan in the Pampangan sub-district. This study uses a qualitative method with a five-stage approach to design thinking according to Tim Brown's version: empathy, define, ideate, prototype, and test. The data collection process was carried out by interviews, observation, literacy, documentation, and questionnaires. The data obtained were then analyzed using the Triadik Sumbo Tinarbuko design concept approach. The results of this synthesis form the basis for designing the Gulo Puan visual brand. The results of the synthesis are also positioned as a solution for the Gulo Puan visual brand for visual communication problems found at the Gulo Puan production center, Pampangan sub-district, South Sumatra Province. The novelty of the results of this design puts forward the concept of Gulo Puan's visual branding as a promotional medium that represents the Gulo Puan gastronomic tourism destination in the Pampangan sub-district. The theory used in this study: visual branding for strategies to design visual branding, sociology theory of design to determine the needs of target audiences, theory of tourist destinations to design tourist destinations, and visual communication design theory is used to design the form of messages and the contents of verbal and visual messages. Conceptually, this research also contributes theoretical and practical knowledge to the development of visual communication design science.